Pengaruh Limbah Cangkang Telur Sebagai Bahan Campuran Pada Kuat Tekan Beton - Pasaribu, Calvin Dionisius; Hermansyah, Hermansyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of using eggshell waste as a mixture in concrete on the resulting compressive strength. Eggshell waste is used as a partial substitute for fine aggregate with variations of 1%, 3%, and 7%. Compressive strength testing was carried out at the age of 14 and 28 days using cylindrical test objects with concrete quality K-150. The results showed that the addition of eggshells affected the compressive strength of concrete, with an increase in compressive strength in the variation of 7% compared to other variations.